Honorary Staff Performance Using Predictors of Commitment, Compensation, and Work Ethic (Study in The Bagian Umum Sekretariat Daerah Pemerintah Kota Kupang) - Jefirstson Richset Riwukore; Luis Marnisah; Jacobus Jermias (Institute of Computer Science (IOCS), 2022)
The purpose of the study was specifically to obtain the results of the analysis of the effect of commitment, compensation and work ethic partially or simultaneously. The research method uses descriptive and verification surveys, and field data collection uses questionnaires, interviews, and documentation techniques. This research is associative research, where in this study there are variables that are related and can influence other variables. The research population was 129 employees who were determined by saturated samples for the determination of respondents so that the entire population became the research sample. Processing data using SPSS 25 analysis tools. The results of this study indicate that the variables of commitment and compensation have a positive and significant effect on performance, while work ethic has no and no significant effect on performance. The results of this study indicate that the three variables consisting of commitment, compensation, and work ethic simultaneously have a positive and significant influence on performance. Thus, these three variables can be used as strategies or predictors for improving employee performance.